Assessing Students Writing Skill 7th grade of STIT Muhammadiyah Tempurejo, Ngawi - Wulandari, Nining (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Assessment is an essential component of effective instruction. Airasian (1996) identified three types of classroom assessments. The first he called "sizing-up" assessments, usually done during the first week of school to provide the teacher with quick information about the students when beginning their instruction. The second type, instructional assessments, are used for the daily tasks of planning instruction, giving feedback, and monitoring student progress. The third type he referred to as official assessments, which are the periodic formal functions of assessment for grouping, grading, and reporting. Assessment is the gathering of information about student learning. It can be used for formative purposes, to adjust instruction or summative purposes, to render a judgment about the quality of student work. It is a key instructional activity, and teachers engage in it every day in a variety of informal and formal ways. Students of 7th grade in STIT Muhammadiyah Ngawi shown the variety of learning style on studying writing so that can be affected on their final score concerned in assessing writing skill. The writer hope this article could help them also the lecturer on how to get better score than last semester by doing some steps that must to be apply by the srudents.